Rediscovering America's sacred ground : public religion and pursuit of the good in a pluralistic America - McGraw, Barbara A. (SUNY series, religion and American public life., 2003)
"Returning to the ideas of John Locke and the Founders themselves, Barbara A. McGraw examines the debate about the role of religion in American public life and unravels the confounded rhetoric on all sides. She reveals that no group has been standing on proper ground and that all sides have misused terminology (religion/secular), dichotomies (public/private), and concepts (separation of church and state) in ways that have little relevance to the original intentions of the founders. She rediscovers a theology underlying the founding documents of the nation that is neither anyone's particular religion nor one requiring religion."--Jacket